Intelligent phone case / Muhammad Ikmal Johari… [et al.] - Johari, Muhammad Ikmal; Kasim, Muhammad Ghazali; Jailani, Muizzuddin; Rahman, Nurul Liyana; Kamaruzaman, Kamalina Azyyati (2019)
Intelligent Phone Case is defined as unique mobile case design to ease consumer's lifestyle with the unique features package. The Intelligent Phone Case is designed with modern approach, featuring artificial intelligent (AI). The case assists consumer in practicing ergonomic posture with highly handed grip. Adjustable phone dimension enables best fitting for various phone models together with camera and fingerprint sensor for the best camera and fingerprint scanner location as located based on the model. In simple words, the phone case that built with special engineering approach fora better lifestyle.